PENGARUH CIRCUIT TRAINING TERHADAP KECEPATAN MEMANJAT PADA PEMANJAT TEBING SUKA-SUKA CLIMBING CLUB JAKARTA UTARA - Sulistianingsih, Syifa Khairunnisa; Achwan, Achwan; Trioclarise, Rovika (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Introduction: Wall climbing requires special physical aspects and skills to increase the athlete's speed. physical Aspects of training and physical ability are not sufficient for success in sports achievement. Circuit training interventions are exercises carried out to increase climbing speed, circuit training exercises in the form of pull up, push up and sit up Purpose: This study was to determine the effect of circuit training on the speed of change. Method: This study used a Quasi-Experimental method, group 1 circuit training and group 2 education with the Two Group Pretest-Posttest research design. This research was conducted at the North Jakarta Sports Hall 3x a week for 4 weeks. The sample is members of the Wall Climbing Club as many as 20 people obtained by means of purposive sampling. Data analysis used statistical tests consisting of the Shapiro-Wilk Test, Paired Sample T- Test, and Independent T-Test. Results: Based on the results of the Paired Sample T-Test statistic in group 1, a p-value of 0.000 (p <0.05) was obtained and in group 2 a p-value of 0.000 (p <0.05). The Independent T-Test results obtained a p-value of 0.039 (p <0.05). Conclusion: There is an effect of circuit training on climbing speed among rock climbers who like North Jakarta wall climbing club